B Cells: The Old New Players in Reproductive Immunology - Fettke, Franziska; Schumacher, Anne; Costa, Serban-Dan; Zenclussen, Ana Claudia (Frontiers in Immunology, 2014)
Reproductive immunology research has long focused on T cell responses to paternal antigens and tolerance mechanisms supporting fetal well-being. The participation of B cells herein was not widely studied. Because of the fascinating immunological uniqueness of pregnancy it is however to be expected that such pleiotropic cells play a considerable role. In fact, on the one hand B cells contribute towards pregnancy tolerance by secreting the immunomodulatory cytokine IL-10 but on the other hand can seriously harm pregnancy because of their capacity of producing autoantibodies. As for protective B cells, new evidences in mouse models arise suggesting that IL-10 producing B cells, the so called B10 cells, help in maintaining tolerance towards semiallogenic fetal antigens. They may be also important to fight danger signals at the fetal- maternal as e.g. in the case of infections with the aim to restore the disrupted fetal tolerance. In human pregnancies, IL-10 producing B cells increase with pregnancy onset but not in the case of spontaneous abortions. In vitro, they are able to suppress TNF-α production by T cells from pregnant individuals. Their generation and functionality will be discussed throughout this review article. B cells can be deleterious to pregnancy as well. Aberrant B cell compartment is associated with obstetric pathologies. In particular the capacity of B2 cells to produce specific autoantibodies or of B1aB cells to secrete natural autoantibodies that can turn autoreactive will be discussed herein.